Metabolic syndrome in indigenous communities in Mexico: a descriptive and cross-sectional study - Mendoza-Caamal, Elvia Cristina (BMC Public Health, 2020)
BACKGROUND: An Amerindian genetic background could play an important role in susceptibility to metabolic diseases, which have alarmingly increased in recent decades. Mexico has one of the highest prevalences of metabolic disease worldwide. The purpose of this study was to determine the prevalence of metabolic syndrome and its components in a population with high Amerindian ancestry. METHODS: We performed a descriptive, quantitative, and analytical cross-sectional study of 2596 adult indigenous volunteers from 60 different ethnic groups. Metabolic syndrome and its components were evaluated using the American Heart Association/National Heart, Lung, and Blood Institute Scientific Statement criteria. RESULTS: The overall prevalence of metabolic syndrome in the indigenous Mexican population was 50.3%. Although females had a higher prevalence than males (55.6% vs. 38.2%), the males presented with combinations of metabolic syndrome components that confer a higher risk of cardiovascular disease. The most frequent metabolic syndrome component in both genders was low HDL-cholesterol levels (75.8%). Central obesity was the second most frequent component in females (61%), though it had a low prevalence in males (16.5%). The overall prevalence of elevated blood pressure was 42.7% and was higher in males than females (48.8 vs. 40%). We found no gender differences in the overall prevalence of elevated triglycerides (56.7%) or fasting glucose (27.9%). CONCLUSIONS: We documented that individuals with Amerindian ancestry have a high prevalence of metabolic syndrome. Health policies are needed to control the development of metabolic disorders in a population with high genetic risk.